Comparison of the Therapeutic Effects and Side Effects of Oral Iron Supplements in Iron Deficiency Anemia - Wu, T.-W.; Tsai, F.-P. (Drug Research, 2016)
Objective: Iron deficiency anemia is an important public health issue, especially for infants, children, and women with menorrhagia. Oral iron supplements are the cheapest, safest, and most effective treatment. This study compared the therapeutic and side effects of ferrous and ferric in iron deficiency anemia.Methods: This was a retrospective study on data collected between April 2012 and October 2013 for patients with iron deficiency anemia who continuously took oral ferric for over one month and then switched to oral ferrous due to poor therapeutic effects. The exclusion criteria were the use of other oral or injected iron preparations, erythropoietin, or vitamin B12.Results: A total of 41 participants were recruited. The average participant age was 44.76±16.89 years; most participants were females (95.1%; 39/41); the average daily dose of oral ferric (139.02±49.39 mg) was higher than that of ferrous (96.34±23.43 mg). Repeated measures: mixed model analyses were conducted to examine patients’ clinical blood test values. The results showed that the mean blood test values for all patients significantly increased after switching to ferrous (p<0.01, with the exception of mean corpuscular hemoglobin). One patient experienced gastrointestinal discomfort and diarrhea after switching to ferrous.Conclusion: This study found that blood test values improved after iron deficiency anemia female patients who displayed poor therapeutic effects with oral ferric switched to ferrous. Literature review showed that the risk for gastrointestinal problems with ferrous is higher than that with ferric. However, no significant difference was found in this study.
Keywords: ferric; ferrous; malnutrition